2020
DOI: 10.31410/tmt.2020.601
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic and Artificial Intelligence Tools in the Context of Tourism Analysis

Abstract: Qualitative and quantitative approaches to multicriteria evaluation and managerial decision- making often ignore the specifics of the role of the human factor. This article summarizes management methods that reflect not only numerical inputs but also data of a qualitative nature while considering their applicability in the tourism sector. Some of them can be assorted within the classes of Artificial intelligence. The focus is on the fuzzy approach at the theoretical and application level. The fuzzy approach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…It was shown that natural attractions, accessibility and port infrastructure, lodging options, and a destination's reputation are the most crucial factors. Subjective rankings of travelers were utilized by Hašková and Horák [54] to determine the level of travel and tourism competitiveness of a country using the fuzzy technique. According to the findings, China has a very high level of competition in the travel and tourist industry compared to the other nations analyzed.…”
Section: Literature Review About Studies On Similar Methods and Subjectsmentioning
confidence: 99%
“…It was shown that natural attractions, accessibility and port infrastructure, lodging options, and a destination's reputation are the most crucial factors. Subjective rankings of travelers were utilized by Hašková and Horák [54] to determine the level of travel and tourism competitiveness of a country using the fuzzy technique. According to the findings, China has a very high level of competition in the travel and tourist industry compared to the other nations analyzed.…”
Section: Literature Review About Studies On Similar Methods and Subjectsmentioning
confidence: 99%